Seroprevalence and seroincidence of Leptospira infection in dogs during a one-year period in an endemic urban area in Southern Brazil - Morikawa, Vivien Midori; Bier, Daniele; Pellizzaro, Maysa; Ullmann, Leila Sabrina [UNESP]; Dexheimer Paploski, Igor Adolfo; Kikuti, Mariana; Langoni, Helio [UNESP]; Biondo, Alexander Welker; Molento, Marcelo Beltrao (Soc Brasileira Medicina Tropical, 2015)
Introduction: Leptospirosis is a zoonosis that affects both humans and animals. Dogs may serve as sentinels and indicators of environmental contamination as well as potential carriers for Leptospira. This study aimed to evaluate the seroprevalence and seroincidence of leptospirosis infection in dogs in an urban low-income community in southern Brazil where human leptospirosis is endemic. Methods: A prospective cohort study was designed that consisted of sampling at recruitment and four consecutive trimestral follow-up sampling trials. All households in the area were visited, and those that owned dogs were invited to participate in the study. The seroprevalence (MAT titers >= 100) of Leptospira infection in dogs was calculated for each visit, the seroincidence (seroconversion or four-fold increase in serogroup-specific MAT titer) density rate was calculated for each follow-up, and a global seroincidence density rate was calculated for the overall period. Results: A total of 378 dogs and 902.7 dog-trimesters were recruited and followed, respectively. The seroprevalence of infection ranged from 9.3% (95% CI; 6.7 - 12.6) to 19% (14.1 - 25.2), the seroincidence density rate of infection ranged from 6% (3.3 - 10.6) to 15.3% (10.8 - 21.2), and the global seroincidence density rate of infection was 11% (9.1 - 13.2) per dog-trimester. Canicola and Icterohaemorraghiae were the most frequent incident serogroups observed in all follow-ups. Conclusions: Follow-ups with mean trimester intervals were incapable of detecting any increase in seroprevalence due to seroincident cases of canine leptospirosis, suggesting that antibody titers may fall within three months. Further studies on incident infections, disease burden or risk factors for incident Leptospira cases should take into account the detectable lifespan of the antibody.
Keywords: Leptospirosis; Dogs; Seroincidence; Seroprevalence; Slum